Sodium Valproate-Induced Chromatin Remodeling - Mello, Maria Luiza S. (Frontiers in Cell and Developmental Biology, 2021)
Valproic acid/sodium valproate (VPA), a drug originally prescribed as an anticonvulsant, has been widely reported to act on epigenetic marks by inducing histone acetylation, affecting the DNA and histone methylation status, and altering the expression of transcription factors, thus leading to modulation of gene expression. All these epigenetic changes have been associated with chromatin remodeling effects. The present minireview briefly reports the main effects of VPA on chromatin and image analysis and Fourier transform infrared (FTIR) microspectroscopy in association with molecular biology methodological approaches to investigate the VPA-induced changes in chromatin structure and at the higher-order supraorganizational level.